CRIMINAL LAW ENFORCEMENT IN EFFORTS TO ERADICATE MONEY LAUNDERING IN INDONESIA - Sari Maharani Tarigan Sibero; Kristiawanto Kristiawanto; Mohammad Ismed (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2024)
Money laundering is an illegal act that aims to hide traces of funds obtained from crime, so that they appear legitimate and legal. Money launderers use a variety of complex methods to evade law enforcement, while still enjoying the proceeds of their crimes. In Indonesia, there are laws designed to prevent and eradicate the criminal offence of money laundering, complemented by various instruments to streamline law enforcement. This research uses the normative juridical method, with qualitative analysis of juridical data in the form of laws and regulations and expert opinions. This research confirms that the formulation of the elements of the crime of money laundering in Articles 3, 4, 5, 6, 7, 8, 9, and 10 of Law No. 8 of 2010 can facilitate the process of investigation, prosecution, and examination. This simpler formulation of unlawful acts allows law enforcement officials to be more effective in taking action against money launderers, especially with regard to corporate legal subjects. Thus, clear and simple regulations can increase the success of law enforcement in dealing with money laundering offences in Indonesia.